The Meaning Of Communication Ritual “Already Sea” As The Sustainability Of Maritim Culture Values Of The Community Village Coconut Islands - muslim muslim (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
This study aims to map the activities, competencies, language, and communication components of the “sea alms” ritual which produces communication patterns as a form of preservation of maritime cultural values in the island community. The concept of ritual communication on which this research is based is ritual. Ritual is a habitual action (hereditary action) and also contains transcendental values. So, it can be understood that rituals are related to voluntary performances carried out by the community from generation to generation (based on habits) regarding patterned behavior. Communication is at the core of interactions between humans who use language in certain cultures. This study uses a qualitative approach with phenomenological methods, an interpretive or qualitative perspective. Ritual as a 'tradition' in the context of communication events and interaction processes. The results of the study reveal that the ritual communication of "alms sea" is an activity of gratitude to God Almighty or the creator, who has provided a fortune from the potential that comes from the sea, this tradition is a form of cultural values that are maintained by fishermen, who live on Pulau Kelapa, dominant is the Bugis community. The ritual "Alms Ocean" is used as a tourist attraction for marine culture, by displaying dance, culinary arts, and typical Bugis cultural symbols which are ornaments of marine tourism attractions.